Enhanced probiotic potential of Lactobacillus kefiranofaciens OSU-BDGOA1 through co-culture with Kluyveromyces marxianus bdgo-ym6 - González-Orozco, Brianda D.; Kosmerl, Erica; Jiménez-Flores, Rafael; Alvarez, Valente B. (Frontiers in Microbiology, 2023)
Due to the increasing consumer demand for the development and improvement of functional foods containing probiotics, new probiotic candidates need to be explored as well as novel means to enhance their beneficial effects. Lactobacillus kefiranofaciens OSU-BDGOA1 is a strain isolated from kefir grains that has demonstrated probiotic traits. This species is the main inhabitant of kefir grains and is responsible for the production of an exopolysaccharide (EPS) whit vast technological applications and potential bioactivities. Research has shown that interkingdom interactions of yeast and lactic acid bacteria can enhance metabolic activities and promote resistance to environmental stressors. Comparative genomic analyses were performed to distinguish OSU-BDGOA1 from other strains of the same species, and the genome was mined to provide molecular evidence for relevant probiotic properties. We further assessed the cumulative effect on the probiotic properties of OSU-BDGOA1 and Kluyveromyces marxianus bdgo-ym6 yeast co-culture compared to monocultures. Survival during simulated digestion assessed by the INFOGEST digestion model showed higher survival of OSU-BDGOA1 and bdgo-ym6 in coculture. The adhesion to intestinal cells assessed with the Caco-2 intestinal cell model revealed enhanced adhesion of OSU-BDGOA1 in co-culture. The observed increase in survival during digestion could be associated with the increased production of EPS during the late exponential and early stationary phases of co-culture that, by enhancing co-aggregation between the yeast and the bacterium, protects the microorganisms from severe gastrointestinal conditions as observed by SEM images. Immune modulation and barrier function for recovery and prevention of flagellinmediated inflammation by Salmonella Typhimurium heat-killed cells (HKSC) in Caco-2 cells were also measured. OSU-BDGOA1 in mono-and co-culture regulated inflammation through downregulation of pro-inflammatory cytokine expression and increased membrane barrier integrity assessed by TEER, FD4 permeability, and expression of tight junctions. The results of the study warrant further research into the application of co-cultures of yeast and LAB in functional probiotic products and the potential to increase EPS production by co-culture strategies.* Values correspond to the mean ± SD. Means without common letter between treatments are significantly different (p < 0.05), Student's t-test.